2022
DOI: 10.1021/acsmacrolett.2c00263
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Enhanced Mechanochemical Activation for Thermal Degrafting of Surface-Tethered Dry Polystyrene Brushes

Abstract: Dry polymer brushes have attracted great attention because of their potential utility in regulating interface properties. However, it is still unknown whether dry polymer brushes will exhibit degrafting behavior as a result of thermal annealing. Herein, a study of the conformational entropy effect on thermal degrafting of dry polystyrene (PS) brushes is presented. For PS brushes with an initial grafting density (σp ini) of 0.61 nm–2, degrafting behavior was observed at 393 K, and the equilibrium σp was approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…As PB may tend to detach from the surface, this issue is one of the limiting factors for using PB in highly specialized devices or large‐scale products. Systematic studies of hydrophilic PB in solution and hydrophobic PB in air provided better understanding of the impact of pH, degree of quaternization, molecular weight and grafting density, as well as temperature on degrafting process 143,144 . As a result, researchers are developing strategies to prevent degrafting, which were summarized and critically reviewed by Yu et al in their recent work 145 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As PB may tend to detach from the surface, this issue is one of the limiting factors for using PB in highly specialized devices or large‐scale products. Systematic studies of hydrophilic PB in solution and hydrophobic PB in air provided better understanding of the impact of pH, degree of quaternization, molecular weight and grafting density, as well as temperature on degrafting process 143,144 . As a result, researchers are developing strategies to prevent degrafting, which were summarized and critically reviewed by Yu et al in their recent work 145 .…”
Section: Discussionmentioning
confidence: 99%
“…Systematic studies of hydrophilic PB in solution and hydrophobic PB in air provided better understanding of the impact of pH, degree of quaternization, molecular weight and grafting density, as well as temperature on degrafting process. 143,144 As a result, researchers are developing strategies to prevent degrafting, which were summarized and critically reviewed by Yu et al in their recent work. 145 Stabilizing PB is an important matter not only to enhance the stability and lifetime of PB layers but also to prevent unnecessary release of micro-and nanoplastics to the environment.…”
Section: High Performance Lubricantsmentioning
confidence: 99%
“…Generally, while ultradense brushes exhibit interfacial properties that could not be otherwise attained by other types of polymer surfaces (including layer-by-layer assemblies or plasma polymerized coatings), significantly high chain crowding could also lead to a series of shortcomings. Among them, it is worth mentioning the intrinsic structural instability by polymer brushes featuring very high values of σ, which was revealed when these are swollen in a good solvent or subjected to thermal treatment . Under these conditions, osmotic pressure might lead to degrafting of polymer chainsfollowing a mechanochemically activated process or detachment of the entire film, which would result in failure of the entire coating. , We can thus derive some general guidelines to be considered as a rule of thumb while designing polymer brushes.…”
Section: Brush Parameters: What Seems To Mattermentioning
confidence: 99%
“…Among them, it is worth mentioning the intrinsic structural instability by polymer brushes featuring very high values of σ, which was revealed when these are swollen in a good solvent 67 or subjected to thermal treatment. 68 Under these conditions, osmotic pressure might lead to degrafting of polymer chains�following a mechanochemically activated process 69−71 �or detachment of the entire film, which would result in failure of the entire coating. 72,73 We can thus derive some general guidelines to be considered as a rule of thumb while designing polymer brushes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Self-assembled monolayers (SAMs) of thiols on gold surfaces are based on thiol–gold chemistry and have been widely used to stabilize and functionalize gold surfaces because of the robust, highly efficient, and easy-to-handle features of the coupling chemistry. The considerable interests in such molecule–metal interfaces are due to versatile applications in anchoring molecules, stabilizing nanoparticles, and labeling or sensing. Although covalent tethering is stable and robust, recent studies have shown that surface-initiated polymerization (SIP) films can be easily detached from the gold surface under largely swelled conditions, which is attributed to the breaking of S–Au interactions. , This undesired cleavage limits the stability and further use of S–Au chemistry in functional materials such as gold nanoparticles or SIP films on gold.…”
mentioning
confidence: 99%